The empirics of Canadian government securities yields - Tanweer Akram; Anupam Das (Levy Economics Institute of Bard College, 2020)
Keynes argued that the short-term interest rate is the main driver of the long-term interest rate. This paper empirically models the relationship between short-term interest rates and long-term government securities yields in Canada, after controlling for other important financial variables. The statistical analysis uses high-frequency daily data from 1990 to 2018. It applies both the cointegration technique and Granger causality within the vector error correction (VEC) framework. The empirical results suggest that the action of the monetary authority is an important determinant of Canadian government securities yields, which supports the Keynesian perspective. These findings have important implications for investors, financial analysts, and policymakers.
Keywords: E43; E50; E60; G10; G12; 330; Canadian Government Bond Yields; Long-Term Interest Rate; Short-TermInterest Rate; Monetary Policy; Cointegration; Granger Causality